Implementation of Abraham Maslow's Humanistic Learning Theory in PAI Learning at SDN Leuwalang - Siti Suriati Sunarti; Khozin (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
Islamic Religious Education (PAI) in elementary schools aims not only to transfer religious knowledge but also to develop student's character and personality holistically. This study describes the implementation of Abraham Maslow's humanistic learning theory in PAI at Leuwalang Elementary School. This theory emphasizes fulfilling students' basic needs as a foundation for self-actualization in learning. Using a qualitative case study approach, data were collected through observation, interviews, and documentation, then analyzed through reduction, presentation, and drawing conclusions. The results show that PAI teachers apply humanistic principles by creating a safe and supportive learning environment, meeting emotional needs, and fostering positive teacher-student relationships. Teachers also encourage self-expression, discussion, and the independent development of spiritual values. The application of Maslow's theory in PAI learning increases student motivation and strengthens understanding of religious values, thus recommending a stronger humanistic approach in Islamic education at the elementary level